Perbandingan Pengaruh Laba dan Value Added pada Return Saham - Wardana, Gentha Putri; Wirama, Dewa Gede (E-Jurnal Akuntansi; Vol 27 No 2 (2019), 2019)
The information of value added is considered to be a better company performance measure and has better association on stock returns compared to earning information that is often used. This study aims to compare the relative information content of earnings and value added in explaining stock returns. This research conducted on all companies listed on the Indonesia Stock Exchange in 2013-2017. 308 samples were taken using random sampling method. The data analysis technique was simple linear regression. It was found that EVA and FVA as proxies of value added outperformed earnings. EVA is also found to be more associated with stock returns compared to FVA. The theoretical implication is in addition to references to further research regarding company performance measurement and stock returns. The practical implications is a matter of consideration for investors to make investment decisions and reference for corporate in financial decision making according to preferences of shareholders. Keywords: Earning, economic value added, financial value added, stock return, relative information content